AGAMA DAN KEADILAN GENDER - Sumbulah, Umi (Pusat Studi Gender UIN Maulana Malik Ibrahim Malang, 2006)
All religions aim to bring justice for all human beings, for men and women. The aim is stated in normative doctrines of each religion. Nonetheles, the interpretation of religious doctrines as well as the religious practices tend to negate universal religious values which respect the equality and justice for both sexes. This reduction is mostly practiced in interpreting the particular texts of doctrines. Consequently, the great meaning of religion is deviated and reduced by subjective interests of the interpreters. Overall, the problem of inequality and injustice is commmonly a result of religious normative doctrines misinterpretation.